2020
DOI: 10.1182/blood-2020-141050
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Selinexor for Acute Myeloid Leukemia: A Systematic Review

Abstract: Introduction: Selinexor, an exportin 1(XPO1) inhibitor has demonstrated anti-leukemia activity as a single agent, as well as in combination regimens for the treatment of acute myeloid leukemia (AML). This systematic review aims to explore the efficacy and safety of selinexor based regimens for the treatment of AML. Methods: A systematic literature search was conducted using PubMed, Embase, Cochrane library, ClinicalTrials.gov, ASCO, and ASH meeting websites. The ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…KPT-330 has been shown to increase in vitro and in vivo the AML-killing efficacy of daunorubicin and other anthracyclins by restoring the nuclear localization of topoisomerase IIα and by downregulating the expression of DNA damage repair genes in AML cells [ 32 ]. These results translated into clinical trials, which showed an increased efficacy of the combination of daunorubicin and cytarabine when used with KPT-330 [ 33 , 34 ]. Taken together, these recent in vivo studies and clinical trials strongly support the effectiveness of our high throughput experimental platform and analysis methodology for the identification of efficacious therapies against AML and validate de efficacy of KPT-330 in combination with daunorubicin for treatment of AML patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…KPT-330 has been shown to increase in vitro and in vivo the AML-killing efficacy of daunorubicin and other anthracyclins by restoring the nuclear localization of topoisomerase IIα and by downregulating the expression of DNA damage repair genes in AML cells [ 32 ]. These results translated into clinical trials, which showed an increased efficacy of the combination of daunorubicin and cytarabine when used with KPT-330 [ 33 , 34 ]. Taken together, these recent in vivo studies and clinical trials strongly support the effectiveness of our high throughput experimental platform and analysis methodology for the identification of efficacious therapies against AML and validate de efficacy of KPT-330 in combination with daunorubicin for treatment of AML patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent clinical trial indicates possible limitations in the efficacy of the combination of daunorubicin and KPT-330 for certain AML patient populations [ 35 ]. Therefore, new effective KPT-330-based drug combinations may be explored since this CRM1 inhibitor has been shown to be more efficacious in clinical trials when used in combination regimes with additional therapeutic agents [ 34 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation